Barriers and facilitators of medication reconciliation through the Consolidated Framework for Implementation Research (CFIR): a systematic review - Fathul Muin; Akbar Eka Nugraha (Faculty of Pharmacy, Universitas Pancasila, 2026)
Medication reconciliation (MedRec) is an intervention that ensures patient safety during healthcare transitions. The Consolidated Framework for Implementation Research (CFIR) was applied to deduce the contextual factors that impact the adoption of MedRec. This systematic review aimed to synthesize evidence on MedRec or pharmacist-led transition-of-care interventions that applied CFIR. A systematic review was conducted according to the PRISMA guidelines. Searches were performed in PubMed, Scopus, and ScienceDirect for studies published between 2000 and 2025 that employed Boolean operators (AND/OR) with keywords (“medication reconciliation” OR “pharmacist-led transition” OR “Pharmacist Discharge Care”) AND (“Consolidated Framework for Implementation Research” OR “CFIR” OR “Implementation Research”). Eligible studies were peer-reviewed, mixed-methods, or implementation research that applied the CFIR to evaluate MedRec. A total of 690 studies were identified and screened by title and abstract, followed by a full-text assessment. Six studies were considered for inclusion after full-text screening. Data were extracted and synthesized narratively, and the findings were mapped across the five CFIR domains. Key facilitators were primarily related to Intervention Characteristics, including adaptability and perceived value, and Inner Setting, including leadership engagement and a supportive organizational culture. The characteristics of individuals included clinical expertise and commitment to medication safety, while effective interprofessional communication supported the implementation across settings. Common barriers were identified within the Inner Setting and Process domains, including limited resources, unclear professional roles, insufficient training, and poor integration of MedRec into existing work flows. The Outer Setting was less frequently reported but reflected patient needs and broader system-level influences. Overall, the CFIR provides a comprehensive framework for understanding the determinants affecting the implementation of MedRec.